Evaluation of the Implementation of Total Quality Management (TQM) at PT. PLN (Persero) ULP Rogojampi - Al-Madani, Bintaniya Zakka; Nugroho, Rusdi Hidayat (Business and Investment Review, 2024)
Total Quality Management (TQM) is a strategic tool used by business people to involve everyone to focus on quality. Organizations that successfully implement Total Quality Management (TQM) are able to improve the perception of quality in the eyes of customers and at the same time reduce costs incurred in the organization. The purpose of this study is to evaluate the implementation of Total Quality Management (TQM) at PT. PLN (Persero) ULP Rogojampi. The analysis method used in this study is descriptive qualitative. The results of this study indicate that Total Quality Management (TQM) at PT. PLN (Persero) ULP Rogojampi has been implemented well. The evaluation conducted based on 10 (ten) main elements of Total Quality Management (TQM) shows that the elements, namely obsession with quality, scientific approach, long-term commitment, teamwork, education and training, controlled freedom, unity of purpose, employee involvement and empowerment have been implemented well by the company. Meanwhile, the elements of focus and continuous system improvement have not been optimally implemented by the company.